Pengembangan Media Pembelajaran Tematik Berbasis Android “Kisah TAYA” untuk Meningkatkan Hasil Belajar Siswa Kelas VI SD - Magdalena Dewi Kusumawati; Mawardi Mawardi (Jurnal Studi Guru dan Pembelajaran, 2021)
To answer the situation in Indonesia and the challenges of 21st century education, this study aims to develop an interactive thematic learning media based on the Android-based Kisah TAYA to improve learning outcomes for students in grade VI SD. The research used is a type of research development or R&D. The subjects of this study were students of grade VI elementary school, but the research only stopped until the expert test and did not practice using the media in the field. This research instrument is in the form of validation sheets for material experts, media experts, and learning design experts. After the validation test was carried out, the results of the material expert validation obtained a score of 75% and was included in the high category. The results of the validation of the instructional media expert obtained a score of 84.2% and it was included in the very high category. And the results of the validation of learning media obtained a score of 81.9% and were included in the very high category. And the conclusion from the results of these categories can be stated that the thematic interactive learning media based on the Android-based TAYA Story is suitable to use.